System threats of the security of business in Kazakhstan - Bolatova, B.Zh.; Tasmaganbetov, A.B; Duissenbayeva, B.B. (BUKETOV BUSINESS REVIEW, 2018)
In article is considered the main objective of a complex security system. From experience it is known that business begins to think of the safety only after there were problems and financial losses. It is possible and it is necessary to avoid. Firstly, it is necessary to tell that complex corporate safety is impossible without providing heads of business with information necessary for comprehensively weighed acceptance of management decisions. If the entity applies for long life and continuous development, the correct handling and the analysis of information on external and internal environment of business and tendencies of market development is necessary. The authors of the article noted that after the security system began to function, the head must constantly monitor the implementation of the provisions of the concept of business security. Providing for the entity of an opportunity to successfully perform the activities in the conditions of instability, to timely distinguish and prevent all potential hazards, to protect by all legal methods the interests, to protect health and life of employees of the entity and national economy is analyzed.